1993
DOI: 10.1111/j.1469-8137.1993.tb03811.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of nitrogen by external hyphae of arbuscular mycorrhizal fungi associated with Zea mays L.

Abstract: SUMMARYThe objective of this study was to examine the ability of arbuscular mycorrhizal (AM) fungi to take up nitrogen from soil and transport it to the host plant. Maize {Zea mays L.) associated with Glomus intraradices Schenck and Smith or left uninoculated was grown in containers which were divided by a nylon net into a root compartment and a hyphal compartment. A 40 /im pore size nylon net was used to exclude plant roots while allowing fungal hyphae to grow into soil confined by the net. ^^N tracer was sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(82 citation statements)
references
References 35 publications
(34 reference statements)
4
74
0
4
Order By: Relevance
“…This can be achieved by using culture vessels where hyphae are separated from the roots by a nylon net, and isolation of the hyphal contribution is attained by mass flow barriers such as air gaps, buffer compartments or perforated plastic barriers. Using such methods, long term N and P transport by external hyphae of arbuscular mycorrhizas has been quantified (Kothari, Marschner & Ro$ mheld, 1991 ;Li, George & Marschner, 1991 ;George et al, 1992 ;Frey & Schu$ epp, 1993 ;Pearson & Jakobsen, 1993 ;Johansen, Jakobsen & Jensen, 1994). To date similar data for ectomycorrhizas are lacking.…”
Section: mentioning
confidence: 99%
“…This can be achieved by using culture vessels where hyphae are separated from the roots by a nylon net, and isolation of the hyphal contribution is attained by mass flow barriers such as air gaps, buffer compartments or perforated plastic barriers. Using such methods, long term N and P transport by external hyphae of arbuscular mycorrhizas has been quantified (Kothari, Marschner & Ro$ mheld, 1991 ;Li, George & Marschner, 1991 ;George et al, 1992 ;Frey & Schu$ epp, 1993 ;Pearson & Jakobsen, 1993 ;Johansen, Jakobsen & Jensen, 1994). To date similar data for ectomycorrhizas are lacking.…”
Section: mentioning
confidence: 99%
“…While elevated CO # stimulated the rate of N # fixation in non-mycorrhizal black locust seedlings, the rate of N absorption by roots was stimulated by CO # enrichment in mycorrhizal seedlings. Several studies have demonstrated that AM fungal hyphae are involved in the N nutrition of host plants, especially in the uptake of NH % + (Ames et al, 1983 ;Barea et al, 1987Barea et al, , 1989Kucey & Bonetti, 1988 ;Johansen et al, 1992Johansen et al, , 1994Frey & Schuepp, 1993). Frey & Schuepp (1993) found that inoculation with AM fungi increased the N uptake of maize plants primarily through hyphal translocation.…”
Section: mentioning
confidence: 99%
“…Several studies have demonstrated that AM fungal hyphae are involved in the N nutrition of host plants, especially in the uptake of NH % + (Ames et al, 1983 ;Barea et al, 1987Barea et al, , 1989Kucey & Bonetti, 1988 ;Johansen et al, 1992Johansen et al, , 1994Frey & Schuepp, 1993). Frey & Schuepp (1993) found that inoculation with AM fungi increased the N uptake of maize plants primarily through hyphal translocation. In an experiment with black locust, mycorrhizal fungi increased plant dependence on the uptake of soil N and decreased plant dependence on N # fixation (K. S. Olesniewicz & R. B.…”
Section: mentioning
confidence: 99%
“…However, in these systems the extent to which extraradical AMF hyphae can contribute to nutrient acquisition of plants remains difficult to determine because of unknown transport by diffusion and mass flow in the soil solution of mobile ions such as nitrate (Johansen et al, 1992(Johansen et al, , 1996Frey & Schu$ epp, 1993). To reduce diffusion and mass flow between the soil compartments, Faber et al (1991) used air gaps, paraffin wax or corn oil barriers, whilst Bethlenfalvay et al (1991) worked with a root-free soil bridge.…”
mentioning
confidence: 99%